Explicamos el origen y expansin del Tahuantinsuyo - Pizarro Marchn, Antonio Francisco (2021)
The present work has as purpose to develop the competence builds historicalinterpretations of the area of Social Sciences, in order to strengthen the participation and the leading role of students in the historical processes so that they explain the origin and expansion of Tahuantinsuyo. The theories that support this work are: the thematic field: that corresponds to the learning purposes of the aforementioned area, which will be developed by the students who are in the National Curriculum of Basic Education. The methodology of this work is based on the search that students carry out on historical processes, interpreting the facts, carrying out a critical-reflective analysis of historical processes, then determining the learning purposes with the teacher so that he applies the pedagogical processes of An intentional way in order to measure learning, in this way the process of planning learning experiences and feedback is defined, allowing the student to describe their achievements and progress in the levels of competence. Among the learning techniques used we have dialogue and debate through the analysis of group work, allowing the development of competence to construct historical interpretations; among the materials used we have readings (annexes), texts, sheets, videos, maps, papers. The results determined that it was possible to train critical, proactive and reflective citizens in the face of the social, environmental and economic problems of their community, students aware of the society where they live and of their role as historical subjects, assuming commitments, becoming agents of change of the Social reality, likewise, it was possible to strengthen teamwork, it was possible to develop the three capacities: critically interpret diverse sources, understand historical time and elaborate explanations on historical processes, of the competence "builds historical interpretations." The present work allowed us to conclude that the competence constructs historical interpretations was developed significantly and the participation and the leading role of students in the historical processes in the "explanation of the origin and expansion of Tahuantinsuyo" was favorably strengthened.